The Muslim world and politics in transition creative contributions of the Gülen movement - Barton, Greg 1962-; Weller, Paul; Yılmaz, İhsan (Bloomsbury Academic, 2013)
The Muslim World and Politics in Transition includes chapters written by international scholars with expertise in relation to the contexts that it addresses. It discusses how the Gulen movement has positioned itself and has sought to contribute within societies - including the movement's home country of Turkey - in which Muslims are in the majority and Islam forms a major part of the cultural, religious and historical inheritance.